An experimental and theoretical approach to the molecular structure of 2-{4-[3-(2,5-dimethylphenyl)-3-methylcyclobutyl]thiazol-2-yl}isoindoline-1,3-dione - Ozdemir, Namik; Dincer, Muharrem; Cukurovali, Alaaddin (Springer, 2010)
The title compound, 2-{4-[3-(2,5-dimethylphenyl)-3-methylcyclobutyl]thiazol-2-yl}isoindoline-1,3-dione (C24H22N2O2S), was synthesized and characterized by IR-NMR spectroscopy and single-crystal X-ray diffraction. The compound crystallizes in the monoclinic space group P2(1)/c with a = 19.7799(13) , b = 6.7473(4) , c = 15.7259(9) and beta = 103.416(5)A degrees. In addition, the molecular geometry, vibrational frequencies and gauge including atomic orbital (GIAO) H-1 and C-13 chemical shift values of the title compound in the ground state have been calculated by using the Hartree-Fock (HF) and density functional method (DFT/B3LYP) with 6-31G(d), 6-31 + G(d,p) and LANL2DZ basis sets, and compared with the experimental data. To determine conformational flexibility, molecular energy profile of the title compound was obtained by semi-empirical (AM1) calculations with respect to two selected degrees of torsional freedom, which were varied from -180A degrees to +180A degrees in steps of 5A degrees. Besides, molecular electrostatic potential, frontier molecular orbitals (FMO) analysis and thermodynamic properties of the title compound were investigated by theoretical calculations.
Keywords: AM1 semi-empirical method; Conformational analysis; DFT; Frontier molecular orbitals; GIAO; HF; IR and NMR spectroscopy; Molecular electrostatic potential; Vibrational assignment; X-ray structure determination